(untitled) (Brazilian Journal of Health Research, 2025)
Introduction: Skin aging drives the search for aesthetic procedures, with hyaluronic acid being a highlight due to its effectiveness and low risk of adverse reactions. However, these procedures can have complications. Factors such as patient characteristics, products used and technique used can influence these complications. With increased interest in cosmetic procedures and the increasing use of social media for information, TikTok® has become a popular platform. Objectives: Analyze how facial fillers and their possible complications were portrayed and shared through videos on TikTok®. Methods: This cross-sectional analytical observational study estimated the frequency of complications related to aesthetic procedures on TikTok®. A preliminary search identified relevant hashtags, resulting in 500 videos, of which 91 were selected following inclusion and exclusion criteria. Data collection took place in 2023 through forms on Google Forms®, investigating views, likes, comments, video source and purpose, complications and affected regions. Results: Most of the videos were published by patients, showing before and after. The engagement of the videos was significant. The most common complication was edema. The most affected anatomical regions were the lips and the periocular region. Conclusion: TikTok® is used to report post-hyaluronic acid facial filler complications by patients and professionals, generating significant engagement. The shared complications reflect those described in the literature, in terms of type and affected area.